Attrition and Reactivation of a Childhood Language: The Case of Returnee Heritage Speakers. (13th May 2019) - Flores, Cristina
Abstract: This article discusses the dynamic nature of childhood bilingualism by analyzing oral speech from returnee heritage speakers (HSs) of Portuguese, who grew up in Germany, but moved to Portugal in childhood/adolescence. The first dataset from 14 speakers showed that the length of exposure to German predicted the rate of (in)accurate production of nominal inflection, indicating that the speakers' morphological knowledge had not been sufficiently stabilized due to the return. The second dataset is from one returnee HS who was reimmersed in the German environment after a 4‐year stay in Portugal. The comparative analysis of the speaker's performance 13 months after moving away from Germany and 11 months after being reexposed to German revealed a significant decrease of inaccurate case, gender, and plural marking, which supports the hypothesis of restabilization of linguistic knowledge. Overall, the findings emphasize the effects of lack of exposure on the development of HSs' bilingual competence. Abstract :